Evaluating energy security in decentralized systems: Review and new index - Omri Carmon; Na’ama Teschner; Shiri Zemah-Shamir; Yael Parag (Energy Strategy Reviews)
This article addresses the limitations of traditional energy security assessment frameworks, such as the World Energy Trilemma Index (WETI) and Energy Transition Index (ETI), in capturing complexities introduced by the decarbonization, decentralization, and digitalization (D3) of national energy systems. The article proposes a refined, D3-compatible index that emphasizes four core elements challenging and expanding conventional notions of energy security: supply-demand variability, distributed system management, supply chain risks, and broader system vulnerabilities. The study employs a systematic three-stage methodology: a targeted literature review, identification of overlooked measurement aspects, and development of refined indicators. The resulting framework utilizes a dashboard approach, introducing adaptive indicators within four categories: “Security of supply and demand,” “Adequacy and stability,” “Operational resilience,” and “Societal resilience.” The German energy transition serves as an illustrative case that demonstrates the practical utility of the new framework. While the index's forward-looking design is fundamentally conceptual, its adaptive structure allows immediate operationalization of selected D3-compatible indicators, as demonstrated in the case study; others lay the groundwork for future empirical applications. This approach significantly advances existing energy security assessment methods, providing policymakers and researchers with a flexible, detailed tool for strategic analysis and informed decision-making in transitioning energy systems.